Sosiologi Masa Lapang: Budaya Konsumerisme Masyarakat Bandar - Sumintak, Sumintak; Muhammad Masruri, (Advances in Humanities and Contemporary Studies, 2022)
This study aims to describe how the consumer culture of urban communities in the midst of the covid 19 pandemic is mostly spent on consumptive activities. The proliferation of several online shopping sites available in the market place has spoiled some consumptive communities in urban areas, especially with the ease of access obtained. Working from home (work from home) creates a change in work culture patterns in the midst of the COVID-19 pandemic, this of course opens up lots of free time opportunities in doing work activities that can be done from home. Then leisure time is an instrument in an effort to reach class in society, which in the end gives birth to excessive consumption as a form of way to express leisure time.Keywords: Sociology, Leisure, Consumerism ABSTRAK            Penelitian ini bertujuan untuk menggambarkan bagaimana budaya konsumerisme masyarakat perkotaan di tengah wabah pandemi covid 19 yang banyak dihabiskan untuk aktifitas konsumtif. Menjamurnya beberapa situs-situs belanja online yang tersedia di market place memanjakan beberapa kalangan masyarakat konsumtif yang ada dikawasan perkotaan terlebih dengan kemudahan akses yang didapatkan. Kerja dari rumah (work from home) menciptakan perubahan pola budaya kerja di tengah wabah pandemi covid 19, hal ini tentunya membuka banyak sekali peluang waktu senggang dalam melakukan aktifias kerja yang dapat dilakukan dari rumah. Kemudian waktu senggang merupakan instrument dalam upaya untuk mencapai kelas dalam masyarakat, yang pada akhirnya melahirkan konsumsi berlebihan sebagai bentuk cara untuk mengekspresikan waktu senggang.